MENGOPTILMALKAN KEMAMPUAN GURU DALAM MENYUSUN RPP DENGAN PENDEKATAN SAINTIFIK - Anang Nazaruddin (WIDYABORNEO, 2021)
The implementation of the 2013 curriculum is an effort to improve education standards in orderto achieve the goals of national education that is able to develop students as a whole in the realm of knowledge, attitudes and skills. In the 2013 Curriculum implementation standard process it is stated that developing aspects of student skills can be done by applying a scientific approach to learning. In order for the implementation of learning with a scientific approach to take place the teacher must be able to design plans for implementing learning with a scientific approach. By understanding the important meaning in the preparation of lesson plans so that learning can take place effectively and efficiently achieve the goals that have been made previously. The preparation of the RPP with a scientific approach consists of 12 principles and 2 stages of activities that begin from reviewing the syllabus to determining the source of learning in accordance with the characteristics of students. The compiled lesson plan starts from the preliminary activities then the core activities consisting of 5 m namely observing, asking questions, gathering information, associating and communicating the results. Then the activity closes by giving positive feedback to students